Relationship between Unsafety Action and Unsafe Conditions with Traffic Accidents in Passenger Car Drivers at Meulaboh Type C Terminal - Ishalyadi Ishalyadi; Muhammad Iqbal Fahlevi; Susy Sriwahyuni; Yolanda Oktaria (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2020)
Traffic accidents according to the World Health Organization are unexpected events that cause injury, damage, and also loss to the owner (victim) and can cause death or injuries both minor injuries and serious injuries. The number of passenger car accidents from Aceh Barat to Banda Aceh through the laneAceh Barat - Aceh Jaya crossing is high from 2018 with 62 cases (63.86%) and 2019 with 64 cases (65.92%) from January to January August. The high number of cases was influenced by driver fatigue, unsafety condition, unsafety action, Length of service and the feasibility of the driver's vehicle. This type of research is quantitative research using cross sectional. The sample method used is total sampling, that is, all populations used as research samples are 48 people.The analysis used is univariate analysis and bivariate analysis. The purpose of this study was to determine the relationship of fatigue, unsafety condition, unsafety action, years of service as well as the eligibility of vehicles with traffic accidents on the driver of passenger cars in Meulaboh type C terminal. The results showed that there was a relationship between unsafety condition and unsafety action with traffic accidents, which was P value <0.05. Hereby it is suggested to the transportation department, the traffic unit, the land transportation organization to cooperate with each other in providing information about factors relating to traffic accidents as well.